About the Structure of the Vortex Flow Around Cylinder With Viscous Fluid - Akhmetov, Rustyam G.; Kutluev, Ruslan R. (Journal of Applied Nonlinear Dynamics, 2026)
he problem of stationary viscous in compressible fluid flow around the cylinder has been analyze d by means of the asymptotic methods. The fluid flow equations are considered in the variables "stream function-a vortex". Asymptotic vortex in the boundary layer near the boundary of the cylinder for average and large Reynolds numbers has been investigated. The equation of the interior boundary layer for stream function has been made by means of using the method of matched asymptotic expansions. The properties solution of the given equation are investigated by means of numerical methods under the additional condition of slipping on the boundary of the cylinder.